Pull-out behaviour of glass-fibre reinforced polymer perforated plate connectors embedded in concrete. Part II: Prediction of load carrying capacity - Lameiras, Rodrigo (2018)
The authors have recently proposed an innovative connector system that consists on a Glass Fibre Reinforced Polymer (GFRP) perforated plate that is embedded into Steel Fibre Reinforced Self Compacting Concrete (SFRSCC) layers. The connection is strongly based in the mechanical interlock assured by the dowels originated from the SFRSCC passing through the holes opened on the GFRP plates. In this study, an analytical framework to evaluate the load capacity of the connections when loaded transversally was developed based on experimental pull-out tests presented in the companion paper (Part I). For a better understanding of the mechanical behaviour of the connections and to allow to make estimations of the load capacity of connection when it is conditioned by the rupture of the connector itself, pull-out pin-bearing tests with single-hole plates were executed to assess the effect of the type of GFRP on the strain distribution in the vicinity of the holes until the failure, as well as the estimated failure modes and load capacities of the connections.